Case Report: Successful Staged Ureteroscopic Treatment of a 5 cm Staghorn Renal Calculus - Joseph M. Ciccone; J. Clinton McCabe; Robert C. Eyre (Case Reports in Urology)
It is widely accepted that percutaneous nephrostolithotorny (PCNL) is the standard of choice for the removal of large staghorn renal calculi. Although data exists supporting a stagad ureteroscopic as an alternate treatment for stones up to 3 cm in select patients, little data exists to support a ureteroscopic approach for stones as large as 5 cm. We present a case of a 68 year old female with a 5 cm staghorn renal calculus managed successfully with a staged ureteroscopic approach. A staged ureteroscopic approach can be effective in treating stones as large as 5 cm.